PENGARUH KOMUNIKASI INTERPERSONAL DAN BUDAYA SEKOLAH TERHADAP MOTIVASI BELAJAR SMK AL IKHWANIYAH TANGERANG SELATAN - Ida Fariastuti (Universitas Prof. Dr. Moestopo (Beragama), 2018)
The purpose of this research is to know the interpersonal communication of teacher and school culture influence to student learning motivation of SMK Al Ikhwaniyah of South Tangerang. This research uses survey method with correlational approach. The variables studied using three variables consist of independent variables of teacher interpersonal communication and school culture, the next variable of student learning motivation. Population in this research is all student of class XI and XII SMK Al Ikhwaniyah Tangerang Selatan academic year 2016-2017 total population 136 student, sample counted 102 student with proportionate random sampling sampling technique. Interpersonal communication of teacher and school culture have positive and significant effect together to student learning motivation with high interpretation level that is 97,5%. This means that increased interpersonal communication of teachers followed by a good school culture will increase student learning motivation.